The False Dichotomy Between ESL and Transitional Bilingual Education Programs: Issues That Challenge All of Us - Kathy Escamilla (Educational Considerations, 1999)
Over the past three decades, the number of culturally and linguistically diverse students in U.S. schools has grown at a rapid rate.